ANALISIS DAN PERANCANGAN SISTEM INFORMASI AKUNTANSI BERBASIS MICROSOFT ACCESS 2019 PADA PERSEDIAAN BARANG DI UD. MAJU MAPAN PACITAN - Nisa, Kharisma Hidayatun; Muntiah, Nur Sayidhatul (Transpublika Publisher, 2024)
UD. Maju Mapan Pacitan is engaged in the production and sale of goods. In running its business, UD. Maju Mapan Pacitan still uses a manual accounting information system, especially in recording inventory, so that information on the inventory of manufactured goods often does not match the physical stock in the warehouse, which complicates the inventory control process. This research aims to design and implement a computerized accounting information system using Microsoft Access. The methods used include observation, interviews, and documentation related to UD. Maju Mapan Pacitan. Data required for design, such as customer data, product types, receipts or invoices, stock records, and inventory-related documents, were collected. The resulting accounting information system includes the main menu, customer form, product data form, production stock form, sales form, filter form, sales report, product in & out report, and production stock report. The new system provides fast and accurate output, minimizes manual recording errors, and produces fast, precise, and accurate merchandise inventory information, supporting the decision-making process.